Evaluation of type of kinematics on glide path procedures and torsional fatigue resistance after preparation of moderately curved canals - Murilo Priori Alcalde; Marco Antonio Hungaro Duarte; Pedro Henrique Souza Calefi; Victor de Moraes Cruz; Bruno Carvalho de Vasconcelos; Marcus Vinícius Reis Só; Rodrigo Ricci Vivan (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: Sixty moderately curved canals of mandibular molars classified as Vertucci's type IV canal configuration were selected by micro-CT 1174. The teeth were divided into two groups according to the kinematics used, whether reciprocating or rotary motion (n=30, totaling 60 mesial root canals). The instruments used to perform the glide path procedures had identical features (0.15 mm of tip size, 0.04 mm/mm taper, thermal treatment, and square cross-section), but differed in the direction of the cutting blade. The duration of the procedure and the absolute and percentage frequency of the instruments to reach the full working length were recorded. The torsional test (3630-1; 1992) was performed on both used and unused instruments, to evaluate a possible reduction in the torsional resistance when using the glide path procedure. Statistical analysis was performed using the unpaired t-test and the chi-square test, and the level of significance was set at 5%. The type of kinematics used affected the duration of glide path procedures, and the reciprocating motion seemed to induce less torsional stress during glide path procedures.